The Influence of Melanin Isolated from Antarctic Yeasts on Cortisol Blood Level in the Rats in conditions of Stress Action - Falalyeyeva, T.M.; Tsyryuk, O.I.; Chyizhanska, N.V.; Zharova, V.P. (Український антарктичний журнал, 2009)
Immobilizational stress, exposure time of which was 24 hour evoked in gastric mucosa of rats formation of ulcers, erosions and hemorrhages with simultaneous drastic increase of cortisol blood level. Melanin defended gastric mucosa against development of injuries evoked by stress and at the same time reduced cortisol blood level by 1,81 times. It was concluded that a decrease in cortisol blood level against a background of melanin action is the result of active influence of melanin on one of the links of mechanism of cortisol liberation.